Analysis of Political Participation of FKIP Students in PEMIRA UMM Reviewed in the Perspective of PPKn - Ramadhon, M. Ilham; Yusuf, Nurbani; Wibowo, Arif Prasetyo (Universitas Tanjungpura, 2025)
Democracy is a system of government used by many countries in the world today, including Indonesia. Higher education institutions serve as a microcosm of state life. As a consequence of a democratic state, Indonesia requires a society that is aware of the importance of political participation. Similarly, campuses also need students who recognize the significance of political participation within the campus. This study employs a qualitative method. Data collection techniques include observation, interviews, and literature review. The political participation of students from the Faculty of Teacher Training and Education in the campus election (Pemira) is relatively low, attributed to various internal and external factors. From a citizenship perspective, students should ideally have a high level of political participation in the Pemira, as it reflects the implementation of three citizenship competencies: civic knowledge, civic skills, and civic disposition. In response to the phenomenon of low political participation among students of the Faculty of Teacher Training and Education, improvements to the Pemira system are necessary for the future. Furthermore, to enhance students' political participation, it is recommended to implement comprehensive and sustainable strategies